In Pursuit of Performance Management Systems in State and Local Government - PATRICIA W. INGRAHAM (The Johns Hopkins University Press, 2007)
The data and other information reported in this book were collected by the Government Performance Project in the years it was located at the Maxwell School of Citizenship and Public Affairs, Syracuse University. The project was funded by The Pew Charitable Trusts. The current iteration of the Government Performance Project, which now focuses only on state governments, is located at the Pew Research Center in Washington, D.C.